2008
DOI: 10.1177/030089160809400611
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of ER, PR, HER-2, CK 5/6, p63 and EGFR Antigen Expression in Medullary Breast Cancer

Abstract: The data from our study seem to be generally comparable with the relatively scarce published data on clinicopathological parameters of MBC and AMBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…IHC-positive staining for ER and PR was considered as greater than or equal to 10% nuclei staining in the invasive component of the tumour [23]. The intensity of the anti-HER2 staining was divided into four grades from 0–3, such that 0 was negative, 1 was slightly positive, 2 was indeterminate and 3 was positive, as previously reported [24].…”
Section: Methodsmentioning
confidence: 99%
“…IHC-positive staining for ER and PR was considered as greater than or equal to 10% nuclei staining in the invasive component of the tumour [23]. The intensity of the anti-HER2 staining was divided into four grades from 0–3, such that 0 was negative, 1 was slightly positive, 2 was indeterminate and 3 was positive, as previously reported [24].…”
Section: Methodsmentioning
confidence: 99%
“…EGFR is found the most important target molecules to date, and a number of studies have confirmed that EGFR is over-expressed in many carcinomas such as breast cancer, non-small cell lung cancer, colorectal cancer and head and neck neoplasm, closely related to proliferation, invasion, metastasis, angiogenesis and apoptosis (O-charoenrat et al, 2002;Matkovic et al, 2008;Molaei et al, 2009;Abusail et al, 2013). But as for SCCO, the studies with respect to EGFR expression, clinicopathological characteristics and prognosis are lack of large sample clinical and pathological data to discuss, and the conclusions are not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were routinely examined for the PR, ER, HER-2, and Ki67 using corresponding antibodies (Zhongshan-Bio Co., Beijing, China). If 10 % or more of the nuclei of the tumor cells were stained, the immunohistochemical staining for ER and PR was regarded as positive [18]. Positive staining for HER-2 was determined by the proportion of positive tumor cells and the density of membrane staining.…”
Section: Patients and Clinical Samplesmentioning
confidence: 99%